Sensory room in a psychiatric intensive care unit. (1st April 2020) - Davies, Rebecca; Murphy, Kenneth; Sethi, Faisil
Background: The use of sensory-based treatment developed in paediatric and neurodevelopment care is a relatively new practice in psychiatric intensive care and acute mental health settings. This report briefly reviews the literature on the use of sensory rooms in psychiatric intensive care units and acute mental health settings, and outlines the development of a sensory room in a female psychiatric intensive care unit; Method: We provide an account of the process of establishing a sensory room in a psychiatric intensive care unit setting, including considerations, protocol, training and feedback. The literature on sensory room use in psychiatric intensive care and acute mental health settings was reviewed using the PubMed database and Google Scholar for 'grey' literature; Results: Widespread positive patient and staff perspectives on sensory room use in psychiatric settings were identified in the literature. Some studies have identified links between sensory-based care and reduced rates of restrictive practice. Feedback from patients using the sensory room established in the report revealed themes of patients enjoying and valuing the practice, and highlighted the need for patient-centred choice in its provision; Conclusions: This report outlines the development of a sensory room in a female psychiatric intensive care unit and briefly reviews the literature on such, considering its efficacy in both patient experience and possible developments in reducing more restrictive practices in care in this clinical setting. It provides a basis for further evaluation and research on sensory room interventions and their effectiveness in improving clinical outcomes.